Collective action and labour militancy interrupted: Back-to-work legislation and the state of permanent exceptionalism at Air Canada. (February 2020) - Stevens, Andrew; Templeton, Andrew
Using data collected from survey responses and interviews conducted in 2014, this study examines the consequences of back-to-work legislation from the perspective of customer service workers at Air Canada represented by Unifor Local 2002. By examining union attitudes, opinions of strikes, wildcat actions and back-to-work legislation deployed in 2011 and 2012, the study concludes that this type of legislation functioned to protect the interests of the employer in an ongoing process of corporate restructuring. Such ad hoc legislative measures, defined by political economists as 'permanent exceptionalism', further undermines the industrial pluralist regime that is the foundation of Canadian labour relations.